2016
DOI: 10.21577/0100-4042.20160140
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of photocatalytic activity of metalloporphyrin–titanium mixtures in microemulsions

Abstract: Photocatalytic activity of titanium citrate and its water-in-oil microemulsions mix with zinc (II) tetraphenylporphyrin have been studied by means of adding 4-chlorophenol and following its degradation using artificial ultraviolet and visible light. 4-Chlorophenol is degraded in 71 and 86%, respectively, in 30 min with the generation of various intermediaries, whose possible formation mechanisms have been proposed based in the results of this research. The generation of benzene derivatives, different to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Solvation is one of the most important and fundamental factors affecting the reactivity and selectivity of O 2 •– . , Acceleration of the O 2 •– -mediated transformation of PFCAs can be achieved through the choice of solvent, thus it can be of great practical importance. In addition, O 2 •– is involved in many environmentally relevant processes occurring at interfaces and other nonaqueous environments such as microemulsions and natural organic matters. , Under these conditions, its kinetics may not be adequately described with the k values measured in the aqueous solution, and solvation starts to play a pivotal role in its reactivity. Herein, we evaluated the change of O 2 •– nucleophilicity in organic solutions with different concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvation is one of the most important and fundamental factors affecting the reactivity and selectivity of O 2 •– . , Acceleration of the O 2 •– -mediated transformation of PFCAs can be achieved through the choice of solvent, thus it can be of great practical importance. In addition, O 2 •– is involved in many environmentally relevant processes occurring at interfaces and other nonaqueous environments such as microemulsions and natural organic matters. , Under these conditions, its kinetics may not be adequately described with the k values measured in the aqueous solution, and solvation starts to play a pivotal role in its reactivity. Herein, we evaluated the change of O 2 •– nucleophilicity in organic solutions with different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…•− is involved in many environmentally relevant processes occurring at interfaces and other nonaqueous environments such as microemulsions and natural organic matters. 78,79 Under these conditions, its kinetics may not be adequately described with the k values measured in the aqueous solution, and solvation starts to play a pivotal role in its reactivity. Herein, we evaluated the change of O 2…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…a Best results obtained by Madriz and co-workers. 92 Fig. 11 Free-base porphyrin H 2 23, Cu23, Fe23Cl, Mn23OAc and Cu24-Cu27 used to sensitize TiO 2 .…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…The addition of Ti( iv ) to Zn 3 microemulsion increased the photodegradation rate of 4-CP. A few years later, the same authors 92 used the same porphyrin Zn 3 , without CTAB, and found that the best conversion percentage of 4-CP (86%) was obtained using W/O microemulsions of titanium citrate mixed with Zn 3 and irradiation with white light for 30 min.…”
Section: Titanium Oxide-supported Porphyrinsmentioning
confidence: 99%
See 1 more Smart Citation